Initial Public Offering Of PT. Dian Swastika Sentosa Tbk And Its Impact On Coal Mining Productivity - Hartana; Didik Suhariyanto (PT. Global Research Collaboration, 2025)
This study examines the legal aspects of the Initial Public Offering (IPO) of PT Dian Swastatika Sentosa Tbk. and its relationship with coal mining productivity by analyzing compliance with capital market regulations and mineral and coal mining laws, as well as its implications for corporate operational performance. This research uses an empirical legal approach that combines normative analysis of Law No. 8 of 1995 concerning Capital Markets and Law No. 4 of 2009 concerning Mineral and Coal Mining (as amended by Law No. 3 of 2020), together with empirical data derived from company annual reports, IPO prospectus documents, and related institutional information obtained from relevant agencies and public disclosures. The findings indicate that PT Dian Swastatika Sentosa Tbk. conducted the IPO process in accordance with applicable capital market provisions, including preparation, submission of registration statements, public offering, and listing on the Indonesia Stock Exchange, as regulated under Article 70 paragraph (1) of the Capital Market Law. From a legal perspective, the IPO does not conflict with Article 93 of the Mineral and Coal Mining Law, as it does not directly alter the ownership structure of entities holding Mining Business Permits (IUP). The study also identifies that regulatory supervision during the IPO period was conducted under the Capital Market and Financial Institutions Supervisory Agency (Bapepam-LK), while acknowledging that current capital market supervision is under the Financial Services Authority (OJK). The study indicates a potential relationship between a successful IPO and improvements in coal mining operational capacity, particularly through enhanced capital structure, increased investment capability, and accelerated development of mining concession areas. However, this relationship should be interpreted cautiously as it is based on descriptive empirical evidence rather than statistical measurement.